Analysis of Differences in Evaluation and Management Between Traditional Fuel-Powered Used Cars and New Energy Used Cars - Haowen Ren (Journal of World Economy, 2025)
With the rapid growth of new energy vehicles in China, the used-car market is experiencing a transformation. This paper analyzes the differences in evaluation and management between traditional fuel-powered used cars and new energy used cars. The evaluation criteria differ significantly in terms of core components, endurance capacity, usage costs, technological upgrades, market recognition, and detection standards. Traditional fuel-powered used cars focus on engine and transmission performance, while new energy used cars emphasize battery health and efficiency. Moreover, new energy vehicles require specialized detection tools and evolving evaluation standards. Transaction policies and residual value trends vary significantly between the two categories. Understanding these differences is crucial for used-car dealers to adapt to the evolving market and enhance their competitiveness.